MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN KEAKTIFAN DAN BERFIKIR KREATIF BELAJAR SISWA KELAS VII DI SMP RIYADHUS SHOLIHIN - Hasanah, Saudiah; Muhajir; Huda, Nuril (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study was to determine whether there is an influence between the Discovery learning model on learning activeness, to find out whether there is an influence between the Discovery learning model on creative thinking. This study uses quantitative methods, namely the sampling method used is saturated sample, the type of data used is primary data, the data source comes from a questionnaire with a sample size of 27 respondents. the data analysis method used is multiple linear regression analysis using validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, T test, and F test. (1) Activeness has no effect and significant on the Discovery learning model, (2) creative thinking has a positive effect and significant effect on discovery learning, (3) activeness and creative thinking have an effect and no positive and significant effect simultaneously on the Discovery learning model.